Analysis of the Relationships between the Components of Intellectual Capital in the Public Service (Management and Connections Journal, 2024)
The intellectual capital (IC) of a public organization represents the level of knowledge, skills, experiences, competencies, and capacities of its employees. The research aimed to analyze the relationship between the human, relational, and structural capitals that constitute IC from the perspective of public servants. The theoretical approach is based on the components that form intellectual capital: human, structural, and relational capitals. A strong positive correlation was found between technical knowledge and the incentive for innovation. Human capital resources stood out as a strength due to the education and qualification of the servants; however, structural capital requires investments in infrastructure and ICT. Relational capital is seen as essential to improving communication channels with society. As a social contribution, the study highlights ways to improve the efficiency and effectiveness of public services through more efficient management of human, infrastructure, and relational resources, aiming to meet the needs of citizens. The results of this study contribute to the production of information on the need for investments in infrastructure and technology, the promotion of innovation, and knowledge sharing among servants, thereby improving the quality of decision-making in publicorganization management.
Keywords: Strategic resources; Human resources; employee retention; measurement model; systematic literature review.